FEATURES OF FORMING THE SPATIAL AND VOLUMETRIC STRUCTURE OF AIR TRAFFIC CONTROL TOWER BUILDINGS - Agieieva, Galyna (Theory and practice of design, 2025)
One of the indicators of sustainable development in modern airports is the creation of complex planning hubs and facilities that involve advanced technological, structural, and engineering solutions. Among these, a special place is occupied by Air Traffic Control Tower buildings (hereinafter – ATСT). The designed heights of ATСT buildings make them dominant elements in the spatial organization of airports and surrounding aerodrome territories. This increases the demands on form-making and necessitates the selection of appropriate techniques for revealing the form of such structures, which, on the one hand, have a specific technological function, and on the other – can contribute to making ATСT buildings the most characteristic elements of airport development. The aim of this work is to present the results of research into the features of forming the spatial and volumetric structure of ATCT buildings. Methodology. The study is based on the examination and analysis of design, graphic, and photographic materials; design standards; as well as methods and techniques most commonly used in global and domestic practices of designing and constructing high-rise buildings for public and special purposes. Research method – a systematic approach to studying the object as a component of the spatial organization system of airports and their zones of influence. Results. The role of ATCT buildings and their potential locations within the spatial organization of airports has been examined. Key influencing factors on the spatial and volumetric structure (2); and typological characteristics (5) have been identified. The study reveals specific features of architectural form generation and ensuring its integration with the surrounding environment (context). Particular attention is given to ATCT buildings (5) that have been constructed or are planned for construction at Ukrainian airports in the first quarter of the 21st century. Scientific novelty. A technique for creating a stepped compositional structure has been identified, wherein the architectural form of an ATCT building is formed by vertically combining volumetric elements that gradually increase the overall size and volume of the structure. This technique can complement the existing system of architectural form-making methods for high-rise public and special-purpose buildings, and may be used for further research and practical implementation. Practical relevance. The results obtained have been incorporated into the educational process for higher education students in the following specializations: G17 «Architecture and Urban Planning», G18 «Geodesy and Land Management», and G19 «Construction and Civil Engineering» at the State Enterprise «State University «Kyiv Aviation Institute». In particular, they have been used in the development of course programs for the subjects: «Airport Buildings and Structures», «Critical Infrastructure Facilities (Aviation Transport)», «Urban Planning Aspects of Airport Development», «Urbanization of Territories Adjacent to Airports», among others.